2018
DOI: 10.1038/s41394-018-0103-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of self-guided training for the HandbikeBattle on body composition in people with spinal cord injury

Abstract: Self-guided training for the HandbikeBattle led to a large increase in fitness but had a small effect on body composition, e.g., nutrition may play a more important role than exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…Most responders reported benefits, especially in the fitness domain, but also in the domains of health, personal development, and ADL performance. These results are in agreement with improvements in peak power output and peak oxygen uptake [9], peak expiratory flow [9], body composition [8,9], and mental status [10] during training for the HandbikeBattle event. An explanation for these experienced benefits might be that the HandbikeBattle project (free-living training plus event) meets the experiential aspects of participation (autonomy, belongingness, challenge, engagement, mastery, and meaning) [12] better than the regular exercise training programs.…”
Section: Experienced Benefitssupporting
confidence: 81%
See 1 more Smart Citation
“…Most responders reported benefits, especially in the fitness domain, but also in the domains of health, personal development, and ADL performance. These results are in agreement with improvements in peak power output and peak oxygen uptake [9], peak expiratory flow [9], body composition [8,9], and mental status [10] during training for the HandbikeBattle event. An explanation for these experienced benefits might be that the HandbikeBattle project (free-living training plus event) meets the experiential aspects of participation (autonomy, belongingness, challenge, engagement, mastery, and meaning) [12] better than the regular exercise training programs.…”
Section: Experienced Benefitssupporting
confidence: 81%
“…Handcyclists are advised by rehabilitation professionals, e.g., physical therapists, occupational therapists, and physical educators, but they train on their own or with other team members for 5 months prior to the event. Recent studies showed that training for the HandbikeBattle leads to positive short-term effects on physical fitness and physical and mental health [8][9][10]; however, the ultimate goal of the HandbikeBattle is that participants experience positive effects on performance of activities in daily life and in their personal development, and participate in sports on an ongoing basis. Therefore, the aims of this follow-up survey 1.5-5.5 years after the event were to study: (1) experienced benefits of participation in the HandbikeBattle, (2) ongoing sports participation, and (3) experienced barriers and facilitators of current sport participation, and whether these differ between those who were more/less involved in sports 1.5-5.5 years after the event or participated once or multiple times in the event.…”
Section: Introductionmentioning
confidence: 99%
“…All participants are screened and train in self-organizing teams of their rehabilitation center for a period of 4-5 months prior to the HBB event. Data from this project showed that self-regulated handcycle training over a period of five months can increase peak power output (þ17%), peak oxygen uptake (þ7%), peak ventilation (þ9%) and reduce fat mass index (À6.3%), BMI (À2%) and waist circumference (À4%) [65,83,113,114].…”
Section: Health Benefitsmentioning
confidence: 98%
“…The event is accompanied by a longitudinal cohort study that involves all participants each year and follows them in a pre-post rhythm of measurements prior to training, just before the mountain race and up to a year after the event. The measurements are focused on physical and mental capacity, and wellbeing outcomes [110][111][112][113]. Handcycling is assumed to benefit both the shoulder health and the cardio-metabolic condition and beyond that is fun as a sport or recreation outdoor.…”
Section: Handbikebattlementioning
confidence: 99%